2017
DOI: 10.1021/acs.jafc.7b02049
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Simulation Model TWIN-SHIME Shows Differences between Human Urolithin-Metabotypes in Gut Microbiota Composition, Pomegranate Polyphenol Metabolism, and Transport along the Intestinal Tract

Abstract: A TWIN-SHIME system was used to compare the metabolism of pomegranate polyphenols by the gut microbiota from two individuals with different urolithin metabotypes. Gut microbiota, ellagitannin metabolism, short-chain fatty acids (SCFA), transport of metabolites, and phase II metabolism using Caco-2 cells were explored. The simulation reproduced the in vivo metabolic profiles for each metabotype. The study shows for the first time that microbial composition, metabolism of ellagitannins, and SCFA differ between m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 43 publications
10
84
2
2
Order By: Relevance
“…Meanwhile, the largest increase of predicted human disease-related pathways was also shown in ascending colon after AMX exposure (Fig. 2), which clarified that the primary effect observed at the level of the microbiota could also be identified at the genomic and metabolic level, as reported in other researches [49,50]. Furthermore, these AMX effects were still evident for at least two weeks after the AMX discontinuance although the resilient reductions of Klebsiella and human diseaserelated pathways were observed.…”
Section: Amx Effects Were Colon Region-different and Persistentsupporting
confidence: 76%
“…Meanwhile, the largest increase of predicted human disease-related pathways was also shown in ascending colon after AMX exposure (Fig. 2), which clarified that the primary effect observed at the level of the microbiota could also be identified at the genomic and metabolic level, as reported in other researches [49,50]. Furthermore, these AMX effects were still evident for at least two weeks after the AMX discontinuance although the resilient reductions of Klebsiella and human diseaserelated pathways were observed.…”
Section: Amx Effects Were Colon Region-different and Persistentsupporting
confidence: 76%
“…A second adaptation may be the prolonged incubation of the Caco‐2 cells with the (poly)phenolic containing SHIME matrix to a point where a more true‐to‐life in vitro bioavailable profile is obtained, which should be feasible since the cytotoxicity of the SHIME was verified over longer periods (>24 h). With respect to this adaptation, we should also consider that previous research with poly(phenols) and peptides in a similar combined SHIME/Caco‐2 cell transport model, in which samples were taken at more time points than in this study, has demonstrated that the bioactives did not follow linear kinetics, which was assigned to interfering compounds from the digestive matrix …”
Section: Discussionmentioning
confidence: 99%
“…First, the potential of the microbial community to metabolize hesperidin under fed and fasted conditions was investigated using batch incubations (Supporting Information Figures 1 and 2). Next, two units of the SHIME (ProDigest, Belgium) were operated in parallel (TWINSHIME) as described elsewhere . Each setup consisted of five double‐jacketed, constantly stirred vessels at 37 °C under anaerobic conditions, simulating stomach; small intestine (SI); and ascending (AC), transverse (TC), and descending colon (DC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations